Novel pyrochlore-structured bismuth iron antimonates: structural, impedance and electrochemical studies - Jusoh, F. A.; Tan, K. B.; Zainal, Z.; Chen, S. K.; Khaw, C. C.; Lee, O. J.; Balachandran, R.; Ananda Murthy, H. C. (Elsevier, 2021)
A moderate pyrochlore solid solution range of 0.00 ≤ x ≤ 0.64 was observed in the Bi3.36Fe2.08+xSb2.56-xO14.56-x (BFS) system prepared by solid-state reaction at 925 ◦C for 2 days. The overall charge compensation required a one-to-one cationic replacement and oxygen vacancies, i.e. Sb5+ ↔Fe3+ - O2– . BFS cubic pyrochlores showed their refined lattice parameters varying linearly in the range of 10.4284 (8)-10.4513(8), thus obeying the Vegard’s rule. The measured crystallite sizes by both Scherrer and Williamson-Hall methods were found to be in the range of 46–67 nm; whilst, the larger grain sizes in the range of 0.2–2.9 μm were calculated using scanning electron microscopy (SEM) analysis. The AC impedance analysis also verified a few electrical responses of BFS pyrochlores: (i) BFS pyrochlores had moderate dielectric constants in the range of 24–35 and dielectric losses in the order of 10− 1 at room temperature and 1 MHz, (ii) BFS pyrochlores were not electrically homogeneous with bulk capacitances in the order of 10− 12 Fcm− 1 , (iii) a non-Debye type and temperature-dependent relaxation process were discernible and (iv) the movement of charge carrier were either in the long-range or short-range migration subjected to time availability. In addition, BFS pyrochlore thin films had a good capacitive behaviour and electrochemical reversibility, according to the cyclic voltammetry (CV) and galvanostatic charge–discharge (GCD) analyses. All these excellent properties rendered BFS pyrochlores to be a suitable material for Class 1 ceramic capacitors.